Metoga GTAW Welding Joint Strength Study For Aisi 1045 Application Of Milling Tools - Toto Triantoro B W; Waluyo M B (Faculty of Engineering, Andi Djemma University, 2023)
The welding process is a permanent connection process for metal materials using heat energy. The GTAW (Gas Tungsten Arc Welding) welding method is carried out on AISI 1045 steel material with a solid round shape, which has the characteristics and properties of the material slightly above low carbon steel. The welding process was carried out based on AWS A5.18 standard specifications, in this study. by varying the welding amperage between 70, 90, and 110 amperes as well as the ER70S-G series electrodes.To check the results of the welding with the amperage variation, perform tensile testing with standard ASTM A-370 testing, hardness testing using the Vickers method with standard ASTM E-92 testing, microstructure inspection, and grain size calculations as a control for the results of the hardness test. The focus of testing and inspection is carried out in three influential areas, namely, areas of weld metal, HAZ (heat-affected zone), and base metal.The results of this study show that for 70 A welding amperage, the tensile test results in all samples breaking in the weld metal area. While welding amperage 90A broke two samples in the weld metal area, welding amperage 110A broke one sample in the weld metal area. For the results of the hardness test at 110 A amperes, the hardness ratio in the weld metal area to the HAZ area shows that the difference in hardness is not too large compared to the two amperes used, so a welding amperage of 110 A can be recommended. While the results of the microstructure examination in the weld metal area were dominated by pearliet and martensite with a little bainite, the hardness results in the weld metal area were harder compared to the HAZ area and base metal. Likewise, the results of grain size calculations using the Heyn method for regions with higher hardness make the grain sizes appear denser and smaller.